Antimicrobial Stewardship Program for Patients in the Hematological Department Receiving Carbapenem Therapy: A Single-Center and Interrupted Time Series Analysis - Ayako Suzuki; Fumihiro Yamaguchi; Masayuki Maeda; Miyuki Hashiguchi; Nobuyuki Kabasawa; Jun Sasaki; Tokutada Sato; Masaki Fuyama; Yohei Yamazaki; Kei Endo; Kae Iwata; Sei Kobayashi; et al. (MDPI AG, 2023)
As antibiotic resistance has become a global problem, the intervention of an antimicrobial stewardship team (AST) is warranted. In hematological disorders, infectious complications are crucial owing to abnormal neutrophil function and decreased cell-mediated immunity. Despite the widespread implementation of AST intervention, the effectiveness of stewardship practices for immunocompromised patients remains uncertain. We determined the effect of AST interventions on carbapenem therapy in the department of hematology. Patients admitted to the department and undergoing carbapenem therapy were enrolled. We compared carbapenem use between the pre-AST (April 2016-March 2018) and post-AST (April 2018-March 2021) periods. Factors associated with long-term carbapenem therapy were investigated. Overall, 515 episodes of carbapenem therapy in 264 patients in the department were evaluated. According to the interrupted time series analysis, the number of days of therapy decreased with AST intervention (β = −0.263, p = 0.011). In multivariate analysis, predictive factors associated with long-term carbapenem therapy (>8 days) were outpatient onset, chronic obstructive pulmonary disease, acute myeloid leukemia, multiple myeloma, and infection with resistant bacteria (such as extended spectrum β-lactamases and AmpC) (95% confidence interval, 1.030-2.818, 1.067-66.667, 1.057-2.782, 0.168-0.742, and 1.382-5.750, respectively). The AST intervention reduced carbapenem use in patients with hematological disorders.